Information Technology Development in Alumni Search: Validity Analysis - Muslim Muslim; M Giatman; Mukhlidi Muskhir; Hansi Effendi; Dedi Setiawan (invotek, 2022)
Alumni data collection activities as material for recapitulating the data needed as the completeness of accreditation documents and performance evaluation documents for tertiary institutions. This will not be achieved if the data collection is still using manual methods such as contacting the graduates one by one. This activity will take up time and the data that has been collected so far is not optimal. The purpose of conducting this research is to develop information technology in tracing graduates using the Google form at the product validity testing stage. This research is development research using 4D models. The validation test was carried out at the development stage, for this reason, the research was limited to the product development phase only. The instrument used for the validation test is in the form of a validity questionnaire for the product being developed. Questionnaires will be distributed and then the product will be validated based on the statements that have been prepared beforehand. The validators who validate the product are 4 expert lecturers. The assessment is carried out based on material aspects and media aspects. The results of product research developed with an information technology approach are in the valid category. Not until this stage, the product that has been declared valid, then revised again based on suggestions by experts. It is hoped that after obtaining validation data for the product, the next step is to carry out practicality tests and effectiveness tests so that the product can be disseminated and can be used in education, especially in the graduate study tracer at the Department of Automotive Engineering FT-UNP